An Inclusive Early Childhood Education Setting according to Practitioners’ Experiences in Yogyakarta, Indonesia - Evie Jusni; Elina Fonsén; Raisa Ahtiainen (Education Sciences, 2023)
In Indonesia, the definition of inclusive education tends to be a narrow one. Even though the goal of the national policy on inclusive education underlines non-discrimination for all learners, early childhood education (ECE) practices still do not accommodate every child’s needs. This study focuses on inclusive practices in ECE by exploring the provision of inclusive ECE in Yogyakarta, one of the big cities in Indonesia, where ECE inclusive pedagogy has been implemented for more than five years. By exploring ECE practitioners’ experiences, this study aims to discuss the (mis)alignments between inclusive education policy and practices. The data sources are two-fold. First, we conducted online interviews with ECE manager and teachers (N = 5). The second form of data comprised ECE teachers’ online discussions on the topic of inclusion. The data collected were analysed using a thematic analysis method. The results indicate that distributed leadership, an organisational culture that respects diversity, and inclusive ECE pedagogy are the main aspects that need to be developed to enable inclusive ECE.